2013
DOI: 10.1016/j.jmbbm.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte differentiation is regulated by extracellular matrix stiffness and intercellular separation

Abstract: Osteocytes are terminally differentiated bone cells, derived from osteoblasts, which are vital for the regulation of bone formation and resorption. ECM stiffness and cell seeding density have been shown to regulate osteoblast differentiation, but the precise cues that initiate osteoblast–osteocyte differentiation are not yet understood. In this study, we cultured MC3T3-E1 cells on (A) substrates of different chemical compositions and stiffnesses, as well as, (B) substrates of identical chemical composition but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 67 publications
5
95
1
1
Order By: Relevance
“…We attribute this indicative trans-differentiation to the far from physiological substrate stiffness of the PLGA material employed in this study. Indeed, substrate stiffness has been shown to strongly regulate protein expression, cell phenotype maintenance and stem cell differentiation, with soft substrates observed to be neurogenically conductive and rigid substrates to be chondrogenic / osteogenic [73][74][75][76]. This implies that multifactorial, rather than mono-domain, approaches should be assessed in future studies, in accordance with previous observations, where it was suggested that topography should be combined with mechanical loading for physiological bovine tenocyte morphology maintenance [27].…”
Section: Discussionsupporting
confidence: 81%
“…We attribute this indicative trans-differentiation to the far from physiological substrate stiffness of the PLGA material employed in this study. Indeed, substrate stiffness has been shown to strongly regulate protein expression, cell phenotype maintenance and stem cell differentiation, with soft substrates observed to be neurogenically conductive and rigid substrates to be chondrogenic / osteogenic [73][74][75][76]. This implies that multifactorial, rather than mono-domain, approaches should be assessed in future studies, in accordance with previous observations, where it was suggested that topography should be combined with mechanical loading for physiological bovine tenocyte morphology maintenance [27].…”
Section: Discussionsupporting
confidence: 81%
“…Osteocytes are formed when cuboidal-like osteoblasts become embedded within soft secreted osteoid and start to change morphologically to a dendritic shape characteristic of an osteocyte. This transition is accompanied by a loss of cell volume (reduced organelle content) (Knothe Tate et al, 2004;Palumbo et al, 2004) and an increase in the formation and elongation of thin cytoplasmic projections that interconnect with neighbouring osteocytes within the bone ECM and osteoblasts on the surface of the bone (Palazzini et al, 1998;Palumbo, 1986;Mullen et al, 2013;Prideaux et al, 2012;Palumbo et al, 2004). Furthermore, as an osteoblast differentiates to an osteocyte, expression of the osteoblast marker enzyme alkaline phosphatase (ALP) is greatly reduced (Jee, 2001;Mikuni-Takagaki et al, 1995;Nakano et al, 2004) along with an upregulation in dentin matrix protein-1 (DMP-1) (Narayanan et al, 2003;Rios et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Through these methods important cellular responses have been identified, in particular regulatory mechanisms for cell proliferation, Formation of an interconnected osteocyte network migration, and matrix production, which provide information that is driving the development of approaches for regenerating bone tissue in vitro as a treatment for large bone defects. It has been shown that substrate (2D) (Engler et al, 2004;Mullen et al, 2013) and matrix (3D) (Tan et al, 2014) stiffnesses are important physical factors that induce a phenotypic shift towards osteogenic differentiation. Indeed, extracellular mechanical cues are recognised as regulators of a variety of cell behaviours such as migration (Zaman and Trapani, 2006), proliferation (Hadjipanayi et al, 2009), and differentiation (Lo et al, 2000;Tan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations